2013
DOI: 10.1186/2040-2392-4-38
|View full text |Cite
|
Sign up to set email alerts
|

Atypical brain lateralisation in the auditory cortex and language performance in 3- to 7-year-old children with high-functioning autism spectrum disorder: a child-customised magnetoencephalography (MEG) study

Abstract: BackgroundMagnetoencephalography (MEG) is used to measure the auditory evoked magnetic field (AEF), which reflects language-related performance. In young children, however, the simultaneous quantification of the bilateral auditory-evoked response during binaural hearing is difficult using conventional adult-sized MEG systems. Recently, a child-customised MEG device has facilitated the acquisition of bi-hemispheric recordings, even in young children. Using the child-customised MEG device, we previously reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
63
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(72 citation statements)
references
References 65 publications
7
63
2
Order By: Relevance
“…Prolonged activation of CRHR1 in the hippocampus as a result of early stress affects the structure, synaptic function, and cognition (30,31), but we are not aware of any studies that have investigated the sex-specific effect of prenatal (immunological) stress on CRH or its receptors in the hippocampus. Because ASD is associated with changes in lateralization [behavioral study (32), MRI studies (33,34), magnetoencephalography study (35), and references in these studies], and many genes are asymmetrically expressed in the rodent hippocampus (36), we performed Crh, Crhr1, Crhr2, and Crhbp (corticotropin-releasing factor-binding protein) mRNA geneexpression assays on the two hemispheres separately. Because we found the strongest effects on Crhr1 mRNA expression in the left hippocampus, we then continued to investigate histone modifications on the promoter area of the Crhr1 gene in the left hippocampus.…”
mentioning
confidence: 99%
“…Prolonged activation of CRHR1 in the hippocampus as a result of early stress affects the structure, synaptic function, and cognition (30,31), but we are not aware of any studies that have investigated the sex-specific effect of prenatal (immunological) stress on CRH or its receptors in the hippocampus. Because ASD is associated with changes in lateralization [behavioral study (32), MRI studies (33,34), magnetoencephalography study (35), and references in these studies], and many genes are asymmetrically expressed in the rodent hippocampus (36), we performed Crh, Crhr1, Crhr2, and Crhbp (corticotropin-releasing factor-binding protein) mRNA geneexpression assays on the two hemispheres separately. Because we found the strongest effects on Crhr1 mRNA expression in the left hippocampus, we then continued to investigate histone modifications on the promoter area of the Crhr1 gene in the left hippocampus.…”
mentioning
confidence: 99%
“…In previous MEG studies, this component has been alternatively labeled M100 or N100m; we here call this component "N1m." The main sources of the P1m and N1m are the auditory cortex and association cortices, and abnormalities in AEF components have been reported in patients with ASD [1][2][3][4][5][6][7][8][9][10][21][22][23][24][25]. Although many prior studies have focused on the aberrant intensity or latency of AEF components in children with ASD, no investigations have focused on the bilateral synchronization of AEF components in children with ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Altered auditory processing systems in children with ASD have been studied as neurological correlates of some phenotypes in ASD, such as inhibited language acquisition [1][2][3][4][5][6][7][8] and auditory hypersensitivity [9][10][11], and previous studies that have focused on auditory responses of the brain have also demonstrated altered cerebral laterality [2,5,6] and regional connectivity [12] in children with ASD. These studies have indicated alterations in cortical auditory processes in ASD [1,2,4,5,9,10], whereas increased rates of brain stem or peripheral hearing dysfunction have also been reported in the ASD population [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations